Research on Multichannel Test Device of Missile Fuze - Guoyong Zhen; Yanhu Shan; Yiran Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper introduces the design of multichannel acquisition circuit based on FPGA which samples and records the Doppler signals, ignition signal and the working condition of fuze security enforcement agencies of missile fuze in real-time in the test of high speed dynamic intersection. Furthermore, for the problem of increasing number of sample channel which causes the complexity of the multiplexer control, a general programmable channel switching method is proposed based on FPGA. In the method, FPGA is the control core, and using the internal ROM resource effectively simplifies the complexity of channel switch in the multichannel acquisition system. This paper analyzes the acquisition system design, and describes the design of hardware circuit and analog switch address coding in detail. The test result shows that the acquisition circuit meets the design requirements with high sampling precision and application value.